2015
DOI: 10.15560/11.5.1780
|View full text |Cite
|
Sign up to set email alerts
|

Plant diversity on granite/gneiss rock outcrop at Pedra do Pato, Serra do Brigadeiro State Park, Brazil

Abstract: Campo de Altitude, one of the ecosystems associated with the Atlantic Forest, occurs mainly in high plateaus of Southeastern Brazil. The study area is in Serra do Brigadeiro State Park, Southeastern Brazil. We sampled six habitats (swamp field, Vellozia field, high mountain field, scrub slope, high altitude scrub, and cloud forest) that represent three physiognomies (grassland, scrub, and woodland). Overall, 180 species were recorded, belonging to 128 genera and 58 families. The richest families were Orchidace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
(33 reference statements)
1
9
0
Order By: Relevance
“…With regard to the most species rich families our data are consistent with results of other surveys on HAG (Safford, 1999a;Tinti et al, 2015;Campos et al, 2018) as well as other rupestrian vegetation types in Southeastern Brazil (Conceição & Pirani, 2007;Porembski, 2007). We can highlight Asteraceae that generally is the richest family in floristic inventories in all neotropical mountain ecosystems in South and Central America (Safford, 2007).…”
Section: Discussionsupporting
confidence: 89%
“…With regard to the most species rich families our data are consistent with results of other surveys on HAG (Safford, 1999a;Tinti et al, 2015;Campos et al, 2018) as well as other rupestrian vegetation types in Southeastern Brazil (Conceição & Pirani, 2007;Porembski, 2007). We can highlight Asteraceae that generally is the richest family in floristic inventories in all neotropical mountain ecosystems in South and Central America (Safford, 2007).…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, further studies and surveys are required in order to obtain a more widely applicable ecological knowledge. However, we conducted a brief analysis relating to upper montane grasslands of the present study with other vegetation studies about altitude rocky outcrops in Serra da Mantiqueira (Southeastern Brazil) (Caiafa & Silva 2007, Ribeiro et al 2007, Tinti et al 2015 as well as two sites of Serra do Mar (Araras & Madalena) in the State of Rio de Janeiro (Meirelles et al 1999). We learned that neither of the species found in the upper montane grasslands within Serra do Mar in Paraná was found in these two areas in Rio de Janeiro.…”
Section: Structure Of Upper Montane Grasslands In the State Of Paranámentioning
confidence: 84%
“…Perhaps because such species might be more adapted to grasslands than rocky outcrops. Based on studies carried out at Serra da Mantiqueira only two species were found (Caiafa & Silva 2007) to approximately two dozen species (Tinti et al 2015) in common with the ones found within the subranges studied in Paraná, which in addition to the distances between them, may be related to the surrounding phytogeographic aspects. The floristic study reported by Tinti et al (2015) (Serra do Brigadeiro -Mantiqueira, in the State of Minas Gerais) is in alignment with the grasslands of our study, for instance, the following taxa: Achyrocline satureoides, Stevia clausseni, Gaultheria serrata, "Croton mullerianus"(Croton splendidus), Hesperozygis nitida, Lycopodium clavatum, Doryopteris crenulans and Galium hypocarpium.…”
Section: Structure Of Upper Montane Grasslands In the State Of Paranámentioning
confidence: 87%
See 2 more Smart Citations